Waterpipe smoking among health sciences university students: Knowledge, attitude and patterns of use - K.H. Awan; A. Alrshedan; M. Al Kahtani; S. Patil (Elsevier, 2016)
Introduction: Although waterpipe smoking is common in Gulf counties, its prevalence in Saudi Arabia is uncertain. The purposes of this study were (a) to assess the prevalence of waterpipe smoking among healthcare university students in Saudi Arabia and (b) to determine their attitudes and practices of waterpipe smoking. Materials and methods: A cross-sectional survey was conducted among university students of three different health sciences colleges, namely medical, dental, and pharmacy, of a public university, through random cluster sampling. The questionnaire was designed to ask specific questions related to smoking in general and to waterpipe smoking specifically. The study was approved by the institutional research & ethics committees. Results: A total of 535 participants were included in the study. More than one-third of the participants that reported having ever smoked a waterpipe (n = 198, 37%), and the majority of these were current smokers (62.1%, n = 123); dental students were the most common (45.5%, n = 90). Curiosity and pleasure-seeking were the main factors associated with starting waterpipe smoking. About one-sixth (14.9%, n = 80) of the participants failed to identify a single harmful effect, while a vast majority of participants considered waterpipe smoking to be less unhealthy than cigarette smoking. Conclusion: Waterpipe smoking is very popular among Saudi university students, and knowledge among university students about the dangers of waterpipe smoking is alarmingly low. Keywords: Waterpipe smoking, Tobacco, University students, Prevalence, Questionnaire study